The role and status orang Iban women in rural community with special reference to the Ibans of Ng. Mepi, Batang Ai, Sarawak / Josephine Emas Melina - Josephine Emas , Melina (1981)
In societies throughout the world and recorded history, women ' s place and roles have been at home. When we talk of the role and status of women in any given societies we can never overlook their role as a mother, a housewife and as a member of a society: To study the participation of members of a society within a given culture is very important in order to understand fully the human intersection of that society as well as to evaluate the impact of their presence upon their society. This study aim at finding out how far the role and status of the Iban women contribute to the general structure of the Iban community in the rural area/longhouse community.